Issues and concerns of couples presenting for preimplantation genetic diagnosis (PGD). - Katz, MG; Fitzgerald, L; Bankier, A; Savulescu, J; Cram, D (2002)
BACKGROUND: The use of preimplantation genetic diagnosis (PGD) to select genetically 'normal' human embryos and to transfer them to the uterus of a woman has generated considerable controversy. Debate has occurred over the implications of PGD, sex selection, safety of embryonic manipulation and eugenics. This study evaluates a range of social and moral concerns of couples towards PGD and assisted reproductive technologies (ART) prior to treatment to obtain unbiased authentic attitudes independent of the treatment cycle and the outcome. METHODS: A total of 121 subjects were administered a structured questionnaire after each couple's in vitro fertilization (IVF) or genetic counselling session. Group A consisted of 41 subjects presenting for PGD of single gene disorders (PGD-SG) and group B consisted of 48 subjects undertaking PGD for aneuploidy screening (PGD-AS). A control group consisted of 32 subjects that were about to commence their first IVF cycle. RESULTS AND DISCUSSION: All groups found PGD to be a highly acceptable treatment. They expressed little concern about its extension to testing non-disease states such as sex and they were strongly in favour of a shared decision-making model in which couples have considerable autonomy over decisions about the embryo(s) to transfer. Differences between the groups included issues surrounding the transfer of embryos, restrictions to PGD and the destruction of embryos.